The Advantages of the Phonics Method for Early Childhood Reading Skills - Nur Audina; Siti Ma’muroh; Rima Novia Ulfa (JEdu: Journal of English Education, 2022)
Teaching foreign languages especially reading for early chilhood is more challenging and applying an interesting method is needed to improve their ability. Teachers must have known some of easy and fun methods for early chilhood so that the learning process can run well. One method that can be used is the phonics method. Phonics is a method for teaching reading and writing of the English language by developing the letters of the alphabet and their sounds first for their phonemic awareness and an understanding of the links between these sounds and how to use the letters of the alphabet to represent them. A child learning phonics will see a "p" and know that the sound is "puh." This skill will prove incredibly useful when the child is sounding out unknown words and syllables. The strength of this method is the students are easy to make connections between words and sounds. Besides, they can quickly recognise familiar words and to easily sound out new words they encounter. This paper examines the concept of the phonics teaching method and its effectiveness to develop the reading skill for early chilhood.